2002
DOI: 10.1159/000066655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sertraline Hydrochloride on Cardiac Autonomic Dysfunction in Patients with Hemodialysis-Induced Hypotension

Abstract: Background/Aims: It was previously shown that sertraline hydrochloride treatment improved hemodynamic parameters of patients with dialysis induced hypotension (DIH). The aim of this study was to examine the effect of sertraline on the autonomic functions of patients with DIH. Methods: Ten patients with DIH, 10 hemodialysis patients without DIH and 10 healthy control subjects were included into the study. All of the patients were treated with sertraline 50 mg per day for 4 weeks. Pre-treatment and post-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
2
15
1
1
Order By: Relevance
“…It was demonstrated in many studies that an iv administration of 20 mg/kg during each dialysis reduced the intradialytic hypotension (Perazella, 2001;Lynch et al,2008). There are also studies showing that the use of sertraline, which is a reuptake inhibitor of the selective serotonin, in doses of 50 to 100 mg/day also reduced IDH (Perazella, 2001;Yalcin et al,2003). Midodrine is an α1 agonist.…”
Section: Prevention and Treatment Of Intradialytic Hypotensionmentioning
confidence: 99%
“…It was demonstrated in many studies that an iv administration of 20 mg/kg during each dialysis reduced the intradialytic hypotension (Perazella, 2001;Lynch et al,2008). There are also studies showing that the use of sertraline, which is a reuptake inhibitor of the selective serotonin, in doses of 50 to 100 mg/day also reduced IDH (Perazella, 2001;Yalcin et al,2003). Midodrine is an α1 agonist.…”
Section: Prevention and Treatment Of Intradialytic Hypotensionmentioning
confidence: 99%
“…Previous studies have indicated that selective serotonin reuptake inhibitors have improved symptoms in orthostatic hypotension and neurocardiogenic syncope, and have been used as an alternative treatment in patients who develop intradialytic hypotension [23][24][25][26][27][28][29] . Ultrafiltration performed during hemodialysis seems to be the main factor for the activation of the sympathetic reflex and vasoconstriction, which has the purpose of preserving BP at normal levels.…”
Section: Introductionmentioning
confidence: 99%
“…A small study evaluated measures of heart rate variability response to tilt-table testing in dialysis patients with and without DIH and in healthy control subjects. Four-week treatment with 50 mg of sertraline daily induced a paradoxical reduction in indices of sympathetic modulation and sympathovagal balance in patients with DIH while there was an increase in these indices in patients without DIH and in healthy controls, suggesting that the effects of sertraline on DIH might be related to the improvement in the regulation of the autonomic response to hypovolemia 123 . There have been no reported trials of sertraline for cardiac autonomic neuropathy in stage 4-5 CKD patients.…”
Section: Therapeutic Strategiesmentioning
confidence: 94%